Correlation between vivax malaria infection and iron deficiency in children - Desmansyah Desmansyah; Rini Purnamasari; Theodorus Theodorus; Sulaiman Waiman (Indonesian Pediatric Society, 2015)
Background Iron deficiency is considered to be a major public health problem around the world due to its high prevalence as well as its effect on growth, development, and infection-resistance in children. In malaria-endemic areas, malaria infection is thought to contribute to the occurrence of iron deficiency, by means of hepcidin and hemolysis mechanisms. Objective To assess the prevalence of asymptomatic vivax malaria, compare hemoglobin levels and iron status parameters between vivax malaria-infected and uninfected children, assess the prevalence of iron deficiency, and evaluate a possible correlation between vivax malaria infection and iron deficiency. Methods This cross-sectional study was conducted from February to April 2013 at Sanana City of Sula Islands District, North Maluku. Six parameters were evaluated in 5-11-year-old children: malaria parasite infection, hemoglobin level, serum iron concentration, total iron-binding capacity (TIBC), serum transferrin saturation, and serum ferritin concentration. Results Among 296 children aged 5-11 years, 75 (25.3%) were infected with Plasmodium vivax. In infected children, hemoglobin, serum iron, transferrin saturation, TIBC and serum ferritin were significantly lower than in non-infected children (P<0.01). Using a serum ferritin cut-off of <15 Î¼g/dL, 142 (48.0%) of the children were found to be iron deficient. There was a strong correlation between vivax malaria infection and iron deficiency (OR 3.573; 95%CI 2.03-6.29). ConclusionThe prevalence of asymptomatic vivax malaria infection was 25.3%. The hemoglobin level and iron status parameters in vivax malaria-infected subjects were significantly lower than in uninfected children. The prevalence of iron deficiency was 48.0% for all study subjects. Malaria vivax infection was correlated with iron deficiency in 5-11-year-old children at Sanana City.